HIV and AIDS among adolescents who use drugs: opportunities for drug policy reform within the sustainable development agenda. (27th February 2018) - Tinasti, Khalid
Abstract: Introduction: The international community's commitment to halve by 2015 the HIV transmission among people who inject drugs has not only been largely missed, instead new HIV infections have increased by 30%. Moreover, drug injection remains one of the drivers of new HIV infections due to punitive responses and lack of harm reduction resourcing. In the midst of this situation, adolescents are a forgotten component of the global response to illegal drugs and their link with HIV infection. The Sustainable Development Goals (SDGs) present an opportunity to achieve the global objective of ending AIDS among adolescents who use drugs, by addressing the structural vulnerabilities they face be they economic, social, criminal, health‐related or environmental. Discussion: The implementation of the SDGs presents an opportunity to address the horizontal nature of drug policy and to efficiently address the drugs‐adolescents‐HIV risk nexus. Adolescent‐focused drug policies are linked to goals 1, 3, 4, 10, 16 and 17. Goals 3 and 16 are the most relevant; the targets of the latter link to the criminalization of drug use and punitive policy environments and their impact on adolescents' health and HIV transmission risks. Moreover, it presents an opportunity to include adolescent needs that are missing in the three drug control conventions (1961, 1971 and 1988), and link them with the provisions of the Convention on the Rights of the Child (1989). Finally, the six principles to deliver on sustainable development are also an opportunity to divert adolescents who use drugs away from criminalization and punitive environments in which their vulnerability to HIV is greater. Conclusions: Addressing HIV among adolescents who use drugs is an extremely complex policy issue depending on different sets of binding and non‐binding commitments, interventions and stakeholders. The complexity requires a horizontal response provided by the SDGs framework, starting with the collection of disaggregated data on this specific subgroup. Ending AIDS among adolescents who use drugs requires the implementation of national drugs and HIV plans based on the multi‐sectoral approach and the transformative nature of the SDGs, to provide a comprehensive response to the epidemic among this key affected subgroup.